Short- and long-term mortality after intravenous thrombolysis for acute ischemic stroke: A propensity score-matched cohort with 5-year follow-up. Issue 44 (5th November 2021) - Heo, Nam Hun; Lee, Man Ryul; Yang, Ki Hwa; Hong, Ock Ran; Shin, Ji Hyeon; Lee, Bo Yeon; Lee, Ji Young; Ahn, Jae Min; Oh, Hyuk Jin; Oh, Jae Sang
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: It remains unknown whether intravenous thrombolysis (IVT), thrombectomy, or poststroke antithrombotic medication lower short- and long-term mortality in acute ischemic stroke (AIS). This study aimed to investigate the efficacy of IVT in AIS using propensity score matching, to determine whether IVT could reduce short- and long-term mortality, and to identify risk factors influencing short- and long-term mortality in AIS. During 2013 to 2014, the nationwide Korea Acute Stroke Assessment registry enrolled 14, 394 patients with first-ever recorded ischemic stroke. Propensity score matching was used to match IVT and control cases with a 1:1 ratio. The primary outcome was survival up to 3 months, 1 year, and 5 years, as assessed using Kaplan–Meier estimates and Cox proportional hazards. In total, 1317 patients treated with IVT were matched with 1317 patients not treated with IVT. Survival was higher in the IVT group (median, 3.53 years) than in the non-IVT group (median, 3.37 years, stratified log-rank test, P  < .001). Compared with the non-IVT group, thrombolysis performed within 2 hours significantly reduced the risk of 3-month mortality by 37%, and thrombolysis performed between 2 and 4.5 hours significantly reduced the risk of 3-month mortality by 26%. Thrombectomy significantly reduced the risk of 3-month mortality by 28%. Compared with no poststroke medication, poststroke antiplatelet medication was associated with 51%, 55%, and 52% decreases in 3-month, 1-year, and 5-year mortality risk, respectively. Poststroke anticoagulant medication was associated with 51%, 54%, and 44% decreases in the risk of 3-month, 1-year, and 5-year mortality, respectively. IVT and mechanical thrombectomy showed improvement in short-term survival. To improve long-term outcomes, the use of poststroke antithrombotic medication is important in AIS.